Analytic Geometry - Parabola

Geometry Level 5

Let's make a line through point Q ( 1 , 1 ) Q(1,1) and the line intersects with the parabola y 2 = 4 x y^{2}=4x at point D , E D,E different from point R ( 1 , 2 ) R(1,2) . Line D R DR and E R ER intersect with the line l : y = 2 x + 2 l:y=2x+2 at point M , N M,N respectively.

Find the slope of the line D E DE so that M N |MN| reaches the minimum.


The answer is -1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

David Vreken
Apr 9, 2019

If the line through Q ( 1 , 1 ) Q(1, 1) has a slope of m m , then its equation is y 1 = m ( x 1 ) y - 1 = m(x - 1) , and it intersects the parabola y 2 = 4 x y^2 = 4x at D ( 2 + 2 m 2 m + 1 + m 2 m m 2 , 2 + 2 m 2 m + 1 m ) D(\frac{2 + 2\sqrt{m^2 - m + 1} + m^2 - m}{m^2}, \frac{2 + 2\sqrt{m^2 - m + 1}}{m}) and E ( 2 2 m 2 m + 1 + m 2 m m 2 , 2 2 m 2 m + 1 m ) E(\frac{2 - 2\sqrt{m^2 - m + 1} + m^2 - m}{m^2}, \frac{2 - 2\sqrt{m^2 - m + 1}}{m}) .

The line through R ( 1 , 2 ) R(1, 2) and D D has an equation of y 2 = D y 2 D x 1 ( x 1 ) y - 2 = \frac{D_y - 2}{D_x - 1}(x - 1) or y 2 = 2 3 ( m + 1 m 2 m + 1 ) ( x 1 ) y - 2 = \frac{2}{3}(m + 1 - \sqrt{m^2 - m + 1})(x - 1) and the line through R ( 1 , 2 ) R(1, 2) and E E has an equation of y 2 = E y 2 E x 1 ( x 1 ) y - 2 = \frac{E_y - 2}{E_x - 1}(x - 1) or y 2 = 2 3 ( m + 1 + m 2 m + 1 ) ( x 1 ) y - 2 = \frac{2}{3}(m + 1 + \sqrt{m^2 - m + 1})(x - 1) .

Since M M is on R D RD and y = 2 x + 2 y = 2x + 2 , 2 M x = 2 3 ( m + 1 m 2 m + 1 ) ( M x 1 ) 2M_x = \frac{2}{3}(m + 1 - \sqrt{m^2 - m + 1})(M_x - 1) , or M x = 1 m 2 m + 1 m 1 M_x = \frac{1 - \sqrt{m^2 - m + 1}}{m - 1} , and since N N is on R E RE and y = 2 x + 2 y = 2x + 2 , 2 N x = 2 3 ( m + 1 + m 2 m + 1 ) ( N x 1 ) 2N_x = \frac{2}{3}(m + 1 + \sqrt{m^2 - m + 1})(N_x - 1) , or N x = 1 + m 2 m + 1 m 1 N_x = \frac{1 + \sqrt{m^2 - m + 1}}{m - 1} .

Since M M and N N are on the same line, the slope at which M N |MN| reaches a minimum is equivalent to the slope at which V = M x N x V = M_x - N_x is a minimum. Using substitution, V = M x N x = 1 m 2 m + 1 m 1 1 + m 2 m + 1 m 1 V = M_x - N_x = \frac{1 - \sqrt{m^2 - m + 1}}{m - 1} - \frac{1 + \sqrt{m^2 - m + 1}}{m - 1} or V = 2 m 2 m + 1 m 1 V = -\frac{2\sqrt{m^2 - m + 1}}{m - 1} , which has a minimum when the derivative of V V is equal to 0 0 (since V > 0 V'' > 0 ), or when V = m + 1 ( m 1 ) 2 m 2 m + 1 = 0 V' = \frac{m + 1}{(m - 1)^2 \sqrt{m^2 - m + 1}} = 0 , which solves to m = 1 m = \boxed{-1} .

There is a typing error. The x-coordinate of M should be [1-√(m^2-m+1)]/(m-1) in it's solution step. I also proceeded in this way but got fed up. :)

A Former Brilliant Member - 2 years, 2 months ago

Log in to reply

Thanks, I fixed it!

David Vreken - 2 years, 2 months ago
Raymond Chan
Apr 13, 2019

Let D = ( t 1 2 , 2 t 1 ) D=(t_1^2, 2t_1) and E = ( t 2 2 , 2 t 2 ) E=(t_2^2, 2t_2) , t 1 , t 2 0 t_1, t_2 \ge 0 . Then the equation of D R DR is y 2 x 1 = 2 t 1 2 t 1 2 1 = 2 t 1 + 1 \frac { y-2 }{ x-1 } =\frac { 2{ t }_{ 1 }-2 }{ { { t }_{ 1 } }^{ 2 }-1 } =\frac { 2 }{ { t }_{ 1 }+1 } y = 2 x + 2 t 1 t 1 + 1 y=\frac { 2x+2{ t }_{ 1 } }{ { t }_{ 1 }+1 } D R DR and l l intersect at M M : 2 x + 2 = 2 x + 2 t 1 t 1 + 1 2x+2=\frac { 2x+2{ t }_{ 1 } }{ { t }_{ 1 }+1 } x = 1 t 1 x=\frac{-1}{t_1} and y = 2 ( 1 t 1 ) + 2 = 2 2 t 1 y=2(\frac { -1 }{ { t }_{ 1 } } )+2=2-\frac{2}{t_1} , we have M = ( 1 t 1 , 2 2 t 1 ) M=(\frac{-1}{t_1}, 2-\frac{2}{t_1}) .

Similarly, N = ( 1 t 2 , 2 2 t 2 ) N=(\frac{-1}{t_2}, 2-\frac{2}{t_2}) So M N = ( 1 t 1 1 t 2 ) 2 + ( ( 2 2 t 1 ) ( 2 2 t 2 ) ) 2 |MN|=\sqrt { (\frac { -1 }{ { t }_{ 1 } } -\frac { -1 }{ { t }_{ 2 } } )^ 2+((2-\frac { 2 }{ { t }_{ 1 } } )-(2-\frac { 2 }{ { t }_{ 2 } } ))^ 2 } Simplify, and WLOG, let t 1 < t 2 t_1<t_2 , we get M N = 5 ( 1 t 1 1 t 2 ) |MN|=\sqrt{5}(\frac{1}{t_1}-\frac{1}{t_2}) On the other hand, since Q Q is on D E DE , so m D E = 2 t 1 2 t 2 t 1 2 t 2 2 = 2 t 1 1 t 1 2 1 m_{DE}=\frac { 2{ t }_{ 1 }-2{ t }_{ 2 } }{ { { t }_{ 1 } }^{ 2 }-{ { t }_{ 2 } }^{ 2 } } =\frac { 2{ t }_{ 1 }-1 }{ { { t }_{ 1 } }^{ 2 }-1 } 2 t 1 + t 2 = 2 t 1 1 t 1 2 1 \frac { 2 }{ { t }_{ 1 }+{ t }_{ 2 } } =\frac { 2{ t }_{ 1 }-1 }{ { { t }_{ 1 } }^{ 2 }-1 } 2 t 1 t 2 t 1 t 2 + 2 = 0 2t_1t_2-t_1-t_2+2=0 Now we can use Lagrange Multiplier to do this problem: Let L ( t 1 , t 2 , λ ) = 5 ( 1 t 1 1 t 2 ) λ ( 2 t 1 t 2 t 1 t 2 + 2 ) L(t_1, t_2, \lambda)=\sqrt{5}(\frac{1}{t_1}-\frac{1}{t_2})-\lambda (2t_1t_2-t_1-t_2+2) Take the 3 partial derivatives, set them equal 0, we get { ( 1 ) 5 ( 1 t 1 2 ) λ ( 2 t 2 1 ) = 0 5 + λ ( 2 t 1 2 t 2 t 1 2 ) = 0 ( 2 ) 5 ( 1 t 2 2 ) λ ( 2 t 1 1 ) = 0 5 λ ( 2 t 1 t 2 2 t 2 2 ) = 0 ( 3 ) ( 2 t 1 t 2 t 1 t 2 + 2 ) = 0 2 t 1 t 2 t 1 t 2 + 2 = 0 \begin{cases} (1)\quad \sqrt { 5 } (\frac { -1 }{ { { t }_{ 1 } }^{ 2 } } )-\lambda (2{ t }_{ 2 }-1)=0\quad \Rightarrow \quad \sqrt { 5 } +\lambda (2{ { t }_{ 1 } }^{ 2 }{ t }_{ 2 }-{ { t }_{ 1 } }^{ 2 })=0 \\ (2)\quad \sqrt { 5 } (\frac { 1 }{ { { t }_{ 2 } }^{ 2 } } )-\lambda (2{ t }_{ 1 }-1)=0\quad \Rightarrow \quad \sqrt { 5 } -\lambda (2{ t }_{ 1 }{ { t }_{ 2 } }^{ 2 }-{ { t }_{ 2 } }^{ 2 })=0 \\ (3)\quad -(2{ t }_{ 1 }{ t }_{ 2 }-{ t }_{ 1 }-{ t }_{ 2 }+2)=0\quad \Rightarrow \quad 2{ t }_{ 1 }{ t }_{ 2 }-{ t }_{ 1 }-{ t }_{ 2 }+2=0 \end{cases} (1)-(2), we get λ ( 2 t 1 2 t 2 t 1 2 + 2 t 1 t 2 2 t 2 2 ) = 0 \lambda (2{ { t }_{ 1 } }^{ 2 }{ t }_{ 2 }-{ { t }_{ 1 } }^{ 2 }+2{ t }_{ 1 }{ { t }_{ 2 } }^{ 2 }-{ { t }_{ 2 } }^{ 2 })=0 λ ( 2 t 1 t 2 ( t 1 + t 2 ) ( t 1 2 + t 2 2 ) ) = 0 \lambda (2{ t }_{ 1 }{ t }_{ 2 }({ t }_{ 1 }+{ t }_{ 2 })-({ { t }_{ 1 } }^{ 2 }+{ { t }_{ 2 } }^{ 2 }))=0 λ ( 2 t 1 t 2 ( t 1 + t 2 ) ( t 1 + t 2 ) 2 + 2 t 1 t 2 ) = 0 \lambda (2{ t }_{ 1 }{ t }_{ 2 }({ t }_{ 1 }+{ t }_{ 2 })-{ ({ t }_{ 1 }+{ t }_{ 2 } })^{ 2 }+2{ t }_{ 1 }{ t }_{ 2 })=0 By (3), we have t 1 + t 2 = 2 t 1 t 2 + 2 t_1+t_2=2t_1t_2+2 , so the above equation simplify to λ ( 2 t 1 t 2 ( 2 t 1 t 2 + 2 ) ( 2 t 1 t 2 + 2 ) 2 + 2 t 1 t 2 ) = 0 \lambda (2{ t }_{ 1 }{ t }_{ 2 }(2{ t }_{ 1 }{ t }_{ 2 }+2)-{ (2{ t }_{ 1 }{ t }_{ 2 }+2 })^{ 2 }+2{ t }_{ 1 }{ t }_{ 2 })=0 λ ( 2 t 1 t 2 4 ) = 0 \lambda (-2t_1t_2-4)=0 Obviously, λ 0 \lambda \neq 0 (otherwise by (1), 5 = 0 \sqrt{5}=0 ), so we must have t 1 t 2 = 2 t_1t_2=-2 and t 1 + t 2 = 2 ( 2 ) + 2 = 2 t_1+t_2=2(-2)+2=-2 Finally, recall that m D E = 2 t 1 + t 2 = 2 2 = 1 m_{DE}=\frac{2}{t_1+t_2}=\frac{2}{-2}=\boxed{-1} Remark: One could use second derivative test to verify this indeed minimize M N |MN|

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...